The translatability of revolution Guo Moruo and twentieth-century Chinese culture - Wang, Pu 1980- (Cambridge, Massachusetts Published by the Harvard University Asia Center, 2018)
"The first comprehensive study of the writer, politician, and Marxist historian Guo Moruo, this book explores the dynamics of translation, revolution, and historical imagination in twentieth-century Chinese culture. Leaping between different genres of Guo's works, it interrogates the linkage between translation and historical imagination"--Provided by the publisher.
Part I. The translingual making of a Chinese "zeitgeist": Apostrophe, translatability, and the origins of Guo's lyrical politics -- Translingual practice and a "Caesura of the revolution" -- Poetics, thematics, and time: translating Faust in Revolutionary China -- Part II. Translating antiquity into revolution: Autobiography and historiography -- People's democracy in ancient costume -- Modernizing translations of classical poetry -- Conclusion, or, some final variations.
Wang, Pu May need NAR. Birth Date: 11/2/1980 Phone: 781-736-3287 Email: pwang@brandeis.edu Pu Wang is Assistant Professor of Chinese and the Helaine and Alvin Allen Chair in Literature at Brandeis University.--Data view
Includes bibliographical references and index.
Keywords: Guo, Moruo -- 1892-1978.; Historiography -- China -- History -- 20th century; Marxian historiography -- China -- History -- 20th century; Translators -- China -- History -- 20th century; China -- Intellectual life -- 1949-1976.; China -- Historiography -- History -- 20th century